Anatomic versus non-anatomic resection for hepatocellular carcinoma: A systematic review and meta-analysis. Issue 7 (July 2018) - Moris, Dimitrios; Tsilimigras, Diamantis I.; Kostakis, Ioannis D.; Ntanasis-Stathopoulos, Ioannis; Shah, Kevin N.; Felekouras, Evangelos; Pawlik, Timothy M.
Abstract: Objective: The relative benefit of anatomic resection (AR) versus non-anatomic resection (NAR) of HCC remains poorly defined. We sought to evaluate the available evidence on oncologic outcomes, as well as the clinical efficacy and safety of AR versus NAR performed as the primary treatment for HCC patients. Material and methods: A systematic review and meta-analysis was conducted using Medline, ClinicalTrials.gov and Cochrane library through April 15th, 2017. Only clinical studies comparing AR versus NAR were deemed eligible. Results: A total of 43 studies were considered eligible (total 12, 429 patients: AR, n = 6839 (55%) versus NAR, n = 5590 (45%)). Blood loss was higher among patients undergoing AR (mean difference: +229.74 ml, 95% CI: 97.09–362.38, p = 0.0007), whereas resection margin was slightly wider following AR versus NAR (mean difference: +0.29 cm, 95% CI: 0.15–0.44, p < 0.0001). No difference was noted for perioperative complications (RR: 0.95, 95% CI: 0.81–1.11, p = 0.49) and perioperative mortality (RR: 0.91, 95% CI: 0.43–1.95, p = 0.82). AR was associated with a disease-free survival (DFS) benefit at 1- (HR: 0.79, 95% CI: 0.68–0.92, p = 0.002), 3- (HR: 0.87, 95% CI: 0.78–0.95, p = 0.004) and 5-years (HR: 0.87, 95% CI: 0.82–0.93, p < 0.0001). AR also was associated with a decreased risk of death at 5-years (HR: 0.88, 95% CI: 0.79–0.97, p = 0.01). Conclusion: Despite the high heterogeneity among studies, the data demonstrated that AR had comparable perioperative morbidity and mortality versus NAR. AR seemed to offer an advantage versus NAR in terms of DFS and OS among patients undergoing resection of HCC – especially among patients without cirrhosis. Thus, AR should be considered the preferred surgical option for patients with HCC when feasible.